Relasi Sosial Pemerintah Desa Dengan Lembaga Kemasyarakatan Desa Dalam Pengembangan Kebudayaan Seni Kuda Lumping Di Desa Sepakat Bersatu - Ridwan Ridwan; Siti Maryam; Pipin Wijayanti (Universitas Muara Bungo, 2025)
This study discusses the social relationship between the Village Government and Community Institutions in the development of kuda lumping (a traditional Javanese horse dance) art and culture in Sepakat Bersatu Village, Rimbo Ilir Subdistrict, Tebo Regency. As a form of local cultural heritage, kuda lumping plays an important role in strengthening social ties within the community and reinforcing the village's cultural identity. However, the relationship between village institutions has not been fully synergistic, particularly in terms of funding, the legal status of art organizations, and youth participation. This research employs a qualitative approach with data collection techniques including observation, interviews, and documentation. The findings show that the existence of kuda lumping art in the village has grown due to the enthusiasm of community leaders and the support of the younger generation, rather than initiatives from village institutions. The suboptimal social relationships have resulted in a lack of innovation in performances and limited formal recognition of the art groups. A collaborative strategy between the village government, traditional institutions, and art groups is needed to ensure the sustainability of this cultural art as a local asset. This study recommends strengthening legal support and village budget allocation for the development of community-based cultural arts.